Assessing the influence of electric vehicle charging profile modelling methods. Issue 15 (30th April 2022) - Simolin, Toni; Rautiainen, Antti; Järventausta, Pertti; Rauma, Kalle; Rehtanz, Christian
Abstract: In the scientific literature, it has been a common assumption that electric vehicles (EVs) draw a constant current during the whole charging session. In reality, EV charging profiles are not linear, and the non‐linearities have recently gained more attention. However, a thorough analysis of the influences of different charging profile modelling methods is not yet carried out. This paper aims to fill this gap by comparing experimental measurements of four commercial EVs and results of a developed simulation model that considers different charging profile modelling methods. According to the results, the use of linear charging profiles may lead to notable modelling inaccuracies (error > 30%) whereas the use of measurement‐based non‐linear charging profile models yields relatively accurate results (error mostly ≤ 3.5%). The results also demonstrate that the use of a simple, but justified, bilinear charging profile model is likely to be sufficiently accurate in most scenarios.